2020
DOI: 10.1186/s13018-020-1567-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating opportunities for improved orthopedics outpatient satisfaction: an analysis of Press Ganey® Outpatient Medical Practice Survey responses

Abstract: Introduction:The Press Ganey® Outpatient Medical Practice Survey (PGOMPS) is composed of 10 provider-specific and 15 non-provider-specific questions. Some healthcare systems link PGOMS overall scores to physician reimbursements. The aim of this study was to determine the frequency of patient satisfaction across individual PGOMPS question, the null hypothesis being that there was no variability between the frequency of satisfaction and similar questions. Methods: We reviewed all new patient orthopedic PGOMPS sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The related bibliography presents numerous evidence that patient satisfaction with a medical procedure often has nothing to do with medical services in themselves. Factors include the patient's age, level of education, patient's race and sex, and race and sex of health care professionals he came into contact with, waiting time for an appointment, location of the center, mental state of the patient, as well as the time between providing medical services and conducting a survey [1 ]. The medical services market is inevitably changing.…”
Section: Introductionmentioning
confidence: 99%
“…The related bibliography presents numerous evidence that patient satisfaction with a medical procedure often has nothing to do with medical services in themselves. Factors include the patient's age, level of education, patient's race and sex, and race and sex of health care professionals he came into contact with, waiting time for an appointment, location of the center, mental state of the patient, as well as the time between providing medical services and conducting a survey [1 ]. The medical services market is inevitably changing.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with what has been established in previous studies in other surgical subspecialties. In the orthopedic setting, one of our co-authors, Stephens et al 10 similarly demonstrated that increasing ADI was an independent predictor of lower patient satisfaction. Similarly in the pediatric population, lower Press Ganey scores were shown to be associated with poor SES.…”
Section: Discussionmentioning
confidence: 70%
“…Because of the high ceiling effect and rightward-skew that the PGS has demonstrated in previous studies, “satisfaction” was determined only if a patient gave a perfect total score. 10 This perfect score variable mimics the “Top Box” score reported by the Press Ganey Corporation and represents the percentage of responses with the highest possible score for a particular question or section such as “Very Good” or “Always” responses. This type of Top Box model, similar to what is used in this study, has been utilized in previous otolaryngology patient satisfaction studies.…”
Section: Methodsmentioning
confidence: 99%
“…The results of this study did not support a clear distinction between factors of empathy, trust, and relatedness, a basic psychological need that must be satisfied for people to experience positive development and outcomes (32), which were subsequently collapsed into a single entity of the therapeutic relationship. Conceptually, these factors are similar or at least retain similar descriptors (15,32 -35). Although the development of the survey items was supported by conceptual definitions by an expert group, and the published literature, the results suggest that the patients did not clearly differentiate empathy, trust, and relatedness.…”
Section: Discussionmentioning
confidence: 99%
“…This approach limits the capacity to more specifically determine the factors influencing the patients response (13) and is in contrast to both the complexity and multifactorial nature of patient satisfaction (4,14). Recent studies examining the predictors of patient satisfaction with orthopedic clinic consultations have used generic patient satisfaction questionnaires (15,16).…”
Section: Introductionmentioning
confidence: 99%